A Dynamic Generalization of Tinbergen's Theory of Policy - Preston, A. J. (Review of Economic Studies, 1974)
Journal Article A Dynamic Generalization of Tinbergen's Theory of Policy Get access A. J. Preston A. J. Preston Australian National University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 1, January 1974, Pages 65–74, https://doi.org/10.2307/2296399 Published: 01 January 1974